Respuesta :
Answer:
A
Step-by-step explanation:
Given the 2 equations
x = 3 - y → (1)
5x - 12 = y → (2)
Substitute x = 3 - y into (2)
5(3 - y) - 12 = y ← distribute and simplify left side
15 - 5y - 12 = y
3 - 5y = y ( add 5y to both sides )
3 = 6y ( divide both sides by 6 )
[tex]\frac{3}{6}[/tex] = y, that is
y = 0.5 → A
Answer:
A
Step-by-step explanation:
Plug the first equation into the second equation. 5(3-y)-12=y
15-5y-12=y. Combine like terms. 3-5y=y. Move the -5y to the other side. 3=y+5y which is 3=6y divide and y=1/2 or 0.5